Use of nutritional supplements by Danish elite athletes and fitness customers - Solheim, S. A.; Nordsborg, N. B.; Ritz, C.; Berget, J.; Kristensen, A. H.; Mørkeberg, J. (Scandinavian Journal of Medicine & Science in Sports, 2017)
The nutritional supplement (NS) industry is one of the fastest growing in the world, and NS use in Denmark is among the highest in Europe. However, the exact use in elite athletes and fitness customers targeted for doping control is unknown. Information from 634 doping control forms obtained in 2014 was evaluated (elite athletes: n = 361; fitness customers: n = 273). The majority of female (92.6%) and male (85.0%) elite athletes and female (100.0%) and male (94.0%) fitness customers declared using one or more NS. The use of non-ergogenic NS was more prevalent in women than in men and in younger (15-34 years) compared with older (35-49 years) subjects, but it was less prevalent in intermittent compared with endurance and power/strength sports. Additionally, fitness customers who tested positive for doping also reported using more NS than subjects testing negative, indicating an association between NS and doping abuse. The present results demonstrate a very high prevalence of NS usage in both elite athletes and fitness customers. This highlights the importance of a strong national regulation of NS to avoid contamination of NS with doping substances.